Blockchain records: is the evidence admissible? A challenge for European Member States - Berto, Rebecca (Civil Procedure Review, 2019)
Agreements, transactions and their records play a fundamental role in the economic system of every country: records identify parties, govern their interaction and register events. When agreements are infringed, the aggrieved party would lodge a claim to a court, in order to ask for damages or specific performance. Consequently, the aggrieved party would submit proves in order to found its claim. The digitalization process leads to the creation and storage of digital records. However, digital records are still subject to the same admissibility rules as paper-written documents. Consequently, when digital records are admitted as evidence in legal proceedings, they point out legal ambiguities. These ambiguities are going to be exacerbated by blockchain records because of its technical features. For this reason, the admissibility question of blockchain receipts in legal proceedings is one key point for the future employment of blockchain technology in a country economic system.